The Effect Of Early Mobilization On The Decrease In Fundus Uteri Height Of Postpartum Mothers At UPTD Bawomataluo Health Center - Nehe, Stilistika; Sembiring, Ninsah Mandala Putri (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2023)
In postpartum mothers, uterine involution is a very important process because mothers need special care, assistance and supervision in order to recover health as before pregnancy. If TFU is above normal then this indicates bleeding in the uterus, this is very dangerous if the blood comes out profusely then the mother loses a lot of blood so that there can be shock until death. Early mobilization can speed up the process of lowering TFU, improve blood circulation and prevent the risk of thrombophlebitis. This type of research is a Quasi Experiment study which aims to determine the effect of early mobilization on reducing fundus uteri (TFU) height in Post Partum Mothers at UPTD Bawomataluo Health Center in 2022. The results of the Wilcoxon Signed Rank Test pre-test and post-test data fundus uteri high value with a Z value of 6,780 and a p-value of 0.001 where the p-value is smaller than 0.05 (0.000<0.05), so we can conclude that Ha is accepted and Ho is rejected, which means that there is a difference between the height of the fundus uteri pre-test and post-test early mobilization Mrs. Post Partum. In conclusion, there is an effect of early mobilization on reducing fundus uteri (TFU) height in Post Partum Mothers at UPTD Bawomataluo Health Center. Based on the results of research conducted on the Effect of Early Mobilization on Decreasing the Fundus Uteri Height of Post Partum Mothers at UPTD Bawomataluo Health Center. The fundus uteri (TFU) high value of the pre-test for early mobilization is in the range of 10 cm – 14 cm with the majority of 14 cm, while in the pots-test for early mobilization is in the range of 9 cm – 14 cm with the majority of 12 cm. It is expected that health workers provide education and communication to improve the importance of early mobilization of postpartum mothers.